2007
DOI: 10.1070/pu2007v050n04abeh006227
|View full text |Cite
|
Sign up to set email alerts
|

Mirror particles and mirror matter: 50 years of speculation and searching

Abstract: This review describes the history of discovery of violation of spatial parity P, charge conjugation parity C, combined parity CP. The hypothesis of existence of mirror particles was called upon by its authors to restore the symmetry between left and right. The review presents the emergence and evolution of the concepts "mirror particles" and "mirror matter". It could serve as a concise guide to the "mirror-land". An important part of the review is the list of about 250 references with their titles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(156 citation statements)
references
References 202 publications
(104 reference statements)
1
155
0
Order By: Relevance
“…operators of the schematic form qγ µ γ 5 q × ∂ µ G G G /M 6 . These lead to a lifetime τ 1 +− ∼ 10 s (M/5 TeV) 12 (3 GeV/Λ QCD ) 13 , which is of interest for indirect detection signals as discussed in Section VII.…”
Section: Glueball Metastability and Relic Densitymentioning
confidence: 99%
“…operators of the schematic form qγ µ γ 5 q × ∂ µ G G G /M 6 . These lead to a lifetime τ 1 +− ∼ 10 s (M/5 TeV) 12 (3 GeV/Λ QCD ) 13 , which is of interest for indirect detection signals as discussed in Section VII.…”
Section: Glueball Metastability and Relic Densitymentioning
confidence: 99%
“…We now develop a rudimentary model in which the ρ helps mediate a difference in the radiative n andn β decay rates. The notion of a hidden sector of strongly coupled matter is of some standing [34,35], and has more recently been discussed in the context of models which provide a common origin to baryons and dark matter [36,37], though the mechanism need not be realized through strong dynamics [38,39] -we note Ref. [40] for a recent review.…”
Section: T-odd Correlation In Radiativementioning
confidence: 99%
“…In [2], this idea has been significantly expanded and was later adapted to the framework of the standard model of particle physics [3]. A recent review can be found in [4]. Interactions between ordinary and mirror particles are possible, e.g., they both feel gravity, making mirror matter a viable candidate for dark matter [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%